2001
DOI: 10.1081/jlc-100107356
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Furfural Compounds in Enteral Formula

Abstract: HPLC methods are described for the determination of furanic compounds (hydroxymethylfurfural and furfural) in enteral formulas prepared with dextrinomaltose and milk proteins, and in model systems enclosing these ingredients. These compounds were extracted in aqueous solution, purified with organic solvents, and separated in a reversed-phase C 18 column with water-acetonitrile (95:5 v/v). Average recovery rates of HMF and furfural were 99.2% and 71.1%, respectively. The variation coefficients for HMF and furfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 13 publications
1
20
0
3
Order By: Relevance
“…HMF and furfural determinations were based on those of Rufián-Henares, Guerra-Hernández, and García-Villanova (2001). Briefly, ground sample (500 mg) was suspended in 5 ml of deionised water in a 10-ml centrifuge tube.…”
Section: Hplc Determination Of Hydroxymethylfurfural (Hmf) and Furfuralmentioning
confidence: 99%
“…HMF and furfural determinations were based on those of Rufián-Henares, Guerra-Hernández, and García-Villanova (2001). Briefly, ground sample (500 mg) was suspended in 5 ml of deionised water in a 10-ml centrifuge tube.…”
Section: Hplc Determination Of Hydroxymethylfurfural (Hmf) and Furfuralmentioning
confidence: 99%
“…It was observed that the maximum absorption of HMF is 284 nm. Maximum absorption wavelength of HMF was reported to be in the range of 280-285 nm by other authors (Ameur et al, 2006;Arena, Fallico, & Maccarone, 2001;Ferrer, Alegría, Farré, Abellán, & Romero, 2002;Kalal et al, 2007;Rada-Mendoza, Luz Sanz, Olano, & Villamiel, 2004;Ramírez-Jiménez, Guerra-Hernández, & García-Villanova, 2000;Rufián-Henares, Delgado-Andrade, & Morales, 2006;Rufián-Henares et al, 2001). The chromatograms of all samples were recorded and in order to evaluate the peak purity, they were compared with the chromatograms of standard solutions using the Chemstation software.…”
Section: Determination Of Peak Puritymentioning
confidence: 99%
“…In a more recent study, Durmaz and Gökmen (2010) extracted furan compounds from fat using a methanol-water mixture. In a study by Rufián-Henares, García-Villanova, and Guerra-Hernández (2001), HMF extraction from enteral formula samples was performed by water extraction, followed by extraction with trichloromethane and another extraction with water.…”
Section: Introductionmentioning
confidence: 99%
“…Os AGE estão associados a complicações renais, disfunções endoteliais e patologias neurodegenerativas, processo em que se observa elevada concentração desses compostos, o que possivelmente se relaciona à disfunção neuronal 34 e, ainda, a fatores de risco do desenvolvimento de doenças cardiovasculares 32,[34][35][36][37][38][39] .…”
Section: Efeitos Biológicos Dos Produtos Da Reação De Maillard Ou Da unclassified
“…O consumo de PRM está positivamente associado à síntese de citosinas inflamatórias (TNF-e proteína C reativa) e ao desenvolvimento de nefropatologias, conforme demonstrado em estudos com animais 38,43,45 . Dessa forma, identificar os níveis de PRM em alimentos produzidos e comercializados para pessoas com diabetes e deficiência renal, pode ser uma estratégia que viabiliza a orientação dessa população, contribuindo para a diminuição do risco de desenvolvimento de patologias decorrentes dessa condição de saúde 41,43,45 .…”
Section: Efeitos Biológicos Dos Produtos Da Reação De Maillard Ou Da unclassified